Unusual Pattern of Coeliac Trunk and Its Branches: A Cadaveric Study of Two Cases with its Embryological and Clinical Correlation - Ariyanachi KALIAPPAN; Rohini MOTWANI; Mrudula CHANDRUPATLA (Medeniyet Medical Journal)
The coeliac trunk, the first anterior branch, often originates at the level of the T12 vertebral body, right below the aortic hiatus, as the first ventral branch of the abdominal aorta. It commonly divides into the left gastric, common hepatic, and splenic arteries. We report a rare variation in the branching pattern and course of branches of the coeliac trunk in two donated female cadavers during routine abdominal dissection. It is essential to understand the coeliac trunk and the distinctions in its origin and branching pattern to perform efficient upper abdominal surgical and radiological procedures and to adopt novel interventional and treatment options for hepatic cancers. As anatomists, we are also attempting to link our study's variations to their embryological genesis.